Accreditation in general practice in Denmark: study protocol for a cluster-randomized controlled trial. Issue 1 (December 2017) - Andersen, Merethe; Pedersen, Line; Siersma, Volkert; Bro, Flemming; Reventlow, Susanne; Søndergaard, Jens; Kousgaard, Marius; Waldorff, Frans
Abstract Background Accreditation is used increasingly in health systems worldwide. However, there is a lack of evidence on the effects of accreditation, particularly in general practice. In 2016 a mandatory accreditation scheme was initiated in Denmark, and during a 3-year period all practices, as default, should undergo accreditation according to the Danish Healthcare Quality Program. The aim of this study is primarily to evaluate the effects of a mandatory accreditation scheme. Methods/design The study is conducted as a cluster-randomized controlled trial among 1252 practices (clusters) with 2211 general practitioners in Denmark. Practices allocated to accreditation in 2016 serve as the intervention group, and practices allocated to accreditation in 2018 serve as controls. The selected outcomes should meet the following criteria: (1) a high degree of clinical relevance; (2) the possibility to assess changes due to accreditation; (3) availability of data from registers with no self-reporting data. The primary outcome is the number of prescribed drugs in patients older than 65 years. Secondary outcomes are changes in outcomes related to other perspectives of safe medication, good clinical practice and mortality. All outcomes relate to quality indicators included in the Danish Healthcare Quality Program, which is based on general principles for accreditation. Discussion The consequences of accreditation and standard-setting processes are generally under-researched, particularly in general practice. This is the largest study in general practice with a randomized implementation approach to evaluate the clinical effects of a nation-wide mandatory accreditation scheme in general practice. Trial registration ClinicalTrials.gov, NCT02762240 . Registered on 24 May 2016.